Strategic vertical foreign investment under exchange rate uncertainty - Santanu Roy; Jean-Marie Viaene (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper investigates the strategic incentives for vertical foreign investment by risk-neutral oligopolistic firms and the effect of exchange rate uncertainty on such investment. Firms competing in a domestic final good market meet their input requirements through import. They have the option of investing abroad in a subsidiary and producing their input requirement through such subsidiary, partly or entirely. The other option is to purchase inputs at the market price in the oligopolistic intermediate good market abroad. Exchange rate uncertainty affects the cost of procuring input in both cases. Firms investing upstream can bid up the input price faced by their rivals which do not invest, through strategic purchase. Assuming linear market demand and constant returns technology, we show that an increase in foreign exchange variability has a positive effect on vertical foreign direct investment and on trade in the intermediate good. Further, the incentive to undertake foreign investment may increase when the number of rival firms undertaking such investment increases. This leads to the possibility of multiple equilibria as well as herding in investment decisions; competing firms invest upstream because their rivals do. A small decrease in investment cost can trigger a large increase in investment.
Keywords: D43; F2; F31; 330; vertical foreign investment; foreclosure; exchange rate uncertainty; intra-firm trade